Thermodynamic Study on the Sublimation of Anthracene-Like Compounds - Manuel J S Monte (2010)
A Knudsen mass-loss effusion technique was used for measuring the vapor pressures at different temperatures of the following crystalline compounds: anthraquinone (CAS No. 84-65-1), between (377.06 and 395.03) K; anthrone (CAS No. 90-44-8), between (346.15 and 365.14) K; thianthrene (CAS No. 92-85-3), between (344.27 and 264.06) K; thioxanthone (CAS No. 492-22-8), between (369.12 and 387.20) K; and xanthone (CAS No. 90-47-1), between (342.22 and 362.22) K. From the temperature dependence of the vapor pressure of each crystalline compound, the standard (p degrees = 10(5) Pa) molar enthalpies and Gibbs energies of sublimation, at T = 298.15 K, were derived. The measured thermodynamic properties are compared with literature results for similar compounds, and correlations for estimation of the vapor pressures and enthalpy of sublimation for anthracene-like compounds are presented.